2012
DOI: 10.1037/a0027491
|View full text |Cite
|
Sign up to set email alerts
|

Early adolescent sexual debut: The mediating role of working memory ability, sensation seeking, and impulsivity.

Abstract: Although deficits in working memory ability have been implicated in suboptimal decision making and risk taking among adolescents, its influence on early sexual initiation has so far not been examined. Analyzing 2 waves of panel data from a community sample of adolescents (N = 347; Mean age [baseline] = 13.4 years), assessed 1 year apart, the present study tested the hypothesis that weak working memory ability predicts early sexual initiation and explored whether this relationship is mediated by sensation seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 136 publications
(190 reference statements)
9
63
0
2
Order By: Relevance
“…Discounting is also influenced by resource scarcity . Measures of discounting also show expected correlations with pubertal onset (Khurana et al, 2012).…”
Section: Identifying Psychological Mechanismsmentioning
confidence: 93%
“…Discounting is also influenced by resource scarcity . Measures of discounting also show expected correlations with pubertal onset (Khurana et al, 2012).…”
Section: Identifying Psychological Mechanismsmentioning
confidence: 93%
“…Recent literature has supported the use of the BSSS-4 in regards to risky health behaviors. However, all of those studies required the participant to report their own beliefs (Khurana et al, 2012;Romer & Hennessy, 2007;Stephenson et al, 2003;Vallone, Allen, Clayton, & Xiao, 2007). This study examined parents' perceptions of their child engaging in the BSSS-4 items.…”
Section: Sexuality Education Taught In Schoolsmentioning
confidence: 99%
“…Sensation seeking increases the chance of engaging in risky situations. Several studies have reported that sensation seeking is strongly related to high-risk sexual behaviors among various age groups (Charnigo et al, 2013;Donohew et al, 2000;Gaither & Sellbom, 2003;Hoyle, Stephenson, Palmgreen, Lorch, & Donohew, 2002;Khurana et al, 2012;Spitalnick et al, 2007). A review of the literature found that sensation seeking predicted all forms of sexual risk taking (e.g.…”
mentioning
confidence: 98%
“…Thus these two forms of impulsivity predict independently some of risky behaviors. Investigations indicate that act without thinking associates to risky tendencies to sexual intercourse (Khurana et al, 2012). Yet reduced discounting delay paves the way for a large range of undesirable behaviors.…”
Section: Discussionmentioning
confidence: 99%